Pengaruh Permainan Simulasi Media Kartu Kuartet dan Leaflet terhadap Tingkat Pengetahuan Malaria - Handayani, Endah Purwanti; Lestari, Susi; Astutik, Eftyaningrum Dwi Wahyu (Journal of Telenursing (JOTING), 2024)
This study aims to determine whether there is an influence of quartet card and leaflet media on malaria knowledge in the Youth Posyandu in the working area of the Harapan Sentani Community Health Center. The method used in this research uses a quasi experiment design with a Two Group Pretest Posttest Design. The research results based on the Wilcoxon test obtained p-value= 0.001 < 0.05 with a mean pretest of 5.45 and posttest 9.55 in the quartet card media group and p-value= 0.132 > 0.05 with a mean pretest of 5.05 and posttest 6 .80 in the leaflet group with results from the use of the quartet card game simulation, there was an influence on the level of knowledge of adolescents about malaria compared to the use of leaflets. In conclusion, the quartet card media has a greater influence than the leaflet media on malaria knowledge in the Youth Posyandu in the Harapan Sentani Community Health Center Working Area. Keywords: Quartet Card, Leaflet, Malaria, Knowledge